Olive Leaf Processing for Infusion Purposes - Eva María Ramírez; Manuel Brenes; Concepción Romero; Eduardo Medina (Foods, 2023)
Olive leaf is a by-product rich in bioactive compounds, such as polyphenols and triterpenic acids, with numerous biological activities for human health. Nowadays, the existence of dry olive leaves marketed for infusion elaboration is lacking. During the elaboration process, the drying and grinding stages are critical for the conservation of bioactive compounds, and, precisely, the existing research on olive leaf production procedures is quite scarce. This work aimed to study and model the dehydration process using a forced-air oven and infrared with air convection systems. In addition, different grinding grades were studied. The kinetic constant and activation energy during dehydration were obtained. Drying temperatures above 50 °C produced a decrease in the phenolic concentration of olive leaves; however, it has been observed that prior storage of 24 h at room temperature considerably reduced the loss of phenols. Likewise, it was observed that the higher the degree of grinding, the greater the diffusion of both bioactive compounds and colored compounds. Therefore, the drying and grinding stages were closely related to the content of beneficial compounds and the appearance of the infusions, and their optimization was of crucial importance to produce dried olive leaves rich in biocompounds for use as healthy infusions.